Unilateral climate policy and competitiveness: The implications of differential emission pricing - Christoph Böhringer; Victoria Alexeeva-Talebi (University of Oldenburg, Department of Economics, 2011)
Unilateral emission reduction commitments raise concerns on international competitiveness and emission leakage that result in preferential regulatory treatment of domestic energy-intensive and trade-exposed industries. Our analysis illustrates the potential pitfalls of climate policy design which narrowly focuses on competitiveness concerns about energy-intensive and trade-exposed (EITE) branches. The sector-specific gains of preferential regulation in favour of these branches must be traded off against the additional burden imposed on other industries. Beyond burden shifting between industries, differential emission pricing bears the risk for substantial excess cost in emission reduction as policy concedes (too) low carbon prices to EITE industries and thereby foregoes relatively cheap abatement options in these sectors. From the perspective of global cost-effectiveness we find that differential emission pricing of EITE industries hardly reduces emission leakage since the latter is driven through robust international energy market responses to emission constraints. As a consequence the scope for efficiency compared to uniform pricing is very limited. Only towards stringent emission reduction targets will a moderate price differentiation achieve sufficient gains from leakage reduction to offset the losses of diverging marginal abatement cost.
Keywords: D58; H21; H22; Q48; 330; unilateral climate policy design; leakage; competitiveness